Ultrasonic diagnosis of skin, facial, neck and hand soft tissue in women of different age: a non-randomised observational cross-sectional study - I. N. Bondarenko (Кубанский научный медицинский вестник, 2021)
Background. A dynamic cross-layer visualisation of skin, its vascular structure in various anatomical facets during treatment in different age cohorts holds both scientific and practical value.Objectives. A semiotic study of skin, facial, neck and hand soft tissues using high-resolution ultrasound in women of different age cohorts.Methods. A total of 63 women aged between 22 and 59 years were enrolled. The study was designed with two comparison cohorts. The inclusion criteria were: women aged 22-59 years with no evident somatic or acute dermatological pathology not having aesthetic procedures for at least one month prior to the ultrasound examination of skin, facial, neck and hand soft tissues. The cohorts separated by age. Cohort 1 included 32 women aged 22-44 years (young), and cohort 2 — 31 women aged 45-59 years (middle-aged). High-resolution ultrasound (US) was performed in B-mode, colour Doppler and microV imaging.Results. A maximal dermal thickness was facial middle-third in both cohorts, averaging to 1.87 ± 0.35 mm in the young and 1.57 ± 0.23 — in middle-aged cohort (p <0.0001). A minimal dermal thickness in both cohorts was periorbital (1.16 ± 0.15 mm in the 22-44-year and 0.95 ± 0.12 — in 45-59-year cohort) and in dorsal hand surface (0.89 ± 0.13 and 0.9 ± 0.16 mm, respectively, p <0.0001). The dermal thickness in face and neck diminished with age due to a thinning papillary layer. An adequate dermal vascularisation rate was greater in the young cohort (p = 0.038).Conclusion. Ultrasound is effective in the diagnosis of skin, facial, neck and hand soft tissues at the planning and further control of safe injection and hardware aesthetic procedures, allowing a real-time thickness assessment of epidermis, dermis and its layers, vessels, subcutaneous fat and mimic muscles in norm and during complications.